2019
DOI: 10.1111/ajpy.12264
|View full text |Cite
|
Sign up to set email alerts
|

How to operationalise consciousness

Abstract: Objective: To review the way consciousness is operationalised in contemporary research, discuss strengths and weaknesses of current approaches and propose new measures. Method: We first reviewed the literature pertaining to the phenomenal character of visual and self-consciousness as well as awareness of visual stimuli. We also reviewed more problematic cases of dreams and animal consciousness, specifically that of octopuses. Results: Despite controversies, work in visual and self-consciousness is highly devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 132 publications
(161 reference statements)
0
4
0
Order By: Relevance
“…It is well accepted that consciousness is difficult to measure ( Armstrong, 1898 ; Birch 2022 ; Carruthers et al, 2020 ; Mellor, 2019 ; Sandberg et al, 2010 ). Moreover, it is well established that consciousness is not simply present or absent but varies along a continuum.…”
Section: It Is Possible To Have Consciousness Without Episodic Memorymentioning
confidence: 99%
“…It is well accepted that consciousness is difficult to measure ( Armstrong, 1898 ; Birch 2022 ; Carruthers et al, 2020 ; Mellor, 2019 ; Sandberg et al, 2010 ). Moreover, it is well established that consciousness is not simply present or absent but varies along a continuum.…”
Section: It Is Possible To Have Consciousness Without Episodic Memorymentioning
confidence: 99%
“…Moreover, current evidence of episodic-like memory has been used as supportive evidence for the notion of animal consciousness (Griffin & Speck, 2004), further complicating the usefulness of the current definitions of episodic and episodic-like memory. Recent behavioural work with nonhumans, as well as plants, has further demonstrated that evaluating the presence of consciousness is a complicated topic (Carruthers, Carls-Diamante, Huang, Rosen, & Schier, 2019; Pagán, 2019; Segundo-Ortin & Calvo, 2019; Taiz et al, 2019). Indeed, without turning to self-report, it is difficult to measure consciousness in humans, as the definition of consciousness itself is nebulous at best.…”
Section: Disentangling Episodic Memory From Consciousnessmentioning
confidence: 99%
“…The contrastive analysis established by Baars (1986) is the standard approach for trying to pinpoint the neural events and processes underlying such feelings and experiences. Despite the intimate relationship we all have with our own consciousness, it has proven to be a notoriously difficult task to operationalize it into measurable terms ( Irvine 2012 ; Phillips 2018b ; Carruthers et al. 2019 ; Bayne and Shea 2020 ; Michel 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%